2017
DOI: 10.1016/j.bbi.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of FAAH modulates TLR-induced neuroinflammation, but not sickness behaviour: An effect partially mediated by central TRPV1

Abstract: Aberrant activation of toll-like receptors (TLRs), key components of the innate immune system, has been proposed to underlie and exacerbate a range of central nervous system disorders. Increasing evidence supports a role for the endocannabinoid system in modulating inflammatory responses including those mediated by TLRs, and thus this system may provide an important treatment target for neuroinflammatory disorders. However, the effect of modulating endocannabinoid tone on TLR-induced neuroinflammation in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 85 publications
1
25
0
Order By: Relevance
“…Taken together, the data indicate that the effects of FAAH inhibition on TLR3‐induced inflammatory gene expression are most likely mediated at the level of the brain. Furthermore, we and others have demonstrated that FAAH substrates also potently attenuate TLR4‐induced neuroinflammatory responses in several brain regions, including the hypothalamus (Henry et al, ; Kerr et al, ; Sayd et al, ). Thus, FAAH substrates play an important role in modulating TLR3‐ (and TLR4‐) induced neuroinflammatory responses in both males and females.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Taken together, the data indicate that the effects of FAAH inhibition on TLR3‐induced inflammatory gene expression are most likely mediated at the level of the brain. Furthermore, we and others have demonstrated that FAAH substrates also potently attenuate TLR4‐induced neuroinflammatory responses in several brain regions, including the hypothalamus (Henry et al, ; Kerr et al, ; Sayd et al, ). Thus, FAAH substrates play an important role in modulating TLR3‐ (and TLR4‐) induced neuroinflammatory responses in both males and females.…”
Section: Discussionmentioning
confidence: 76%
“…Both in vitro and in vivo studies have demonstrated that enhancing endocannabinoid tone modulates inflammatory mediators following TLR4 activation (for detailed review, see Henry et al, ). For example, recent studies from our group have demonstrated that inhibition of FAAH and subsequent increases in AEA levels result in an attenuation of TLR4‐induced proinflammatory cytokine responses in several brain regions, including the hypothalamus (Henry et al, ; Kerr et al, ). Furthermore, FAAH substrates, including AEA, have been demonstrated to modulate TLR4‐induced temperature changes and hypophagia (Hollis, Jonaidi, Lemus, & Oldfield, ; Sayd et al, ; Steiner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As previously described [30], animals were singly housed and presented with two drinking bottles in their home cage, one containing tap water and the other containing a 1% (w/v) sucrose solution for 3 days prior to the experiment and for 24hrs following poly I:C/saline injection.…”
Section: Sucrose Preference Testmentioning
confidence: 99%
“…In order to evaluate the effect of URB597 on TLR3-induced neuroinflammation, the expression of CD11b and GFAP were examined in the hypothalamus 24hrs post poly I:C, as markers of microglia/macrophage and astrocyte activation [17,30]. The hypothalamus was selected as it is a key brain region involved in the inflammatory and sickness response to infection, including the viral TLR3-mediated response.…”
Section: Expression Of Markers Of Glial Activation Using Quantitativementioning
confidence: 99%
See 1 more Smart Citation